Analysis of Fuel Supply Control (Palm Shell) Using EOQ Method in Pt. Charoen Pokphand Indonesia Tbk - Abdul Rasyid; Widawati, Enny; Bachtiar W , Marsellinus (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
PT. Charoen Pokphand Indonesia Tbk. (Gorontalo) is still experiencing problems in managing fuel supply where the company often experiences a lack of inventory that hinders the production process. The company also experienced excess inventory, causing storage costs to rise. For this reason, companies need to exercise inventory control. One of the analytical tools that can be used to control inventory is the "Economic Order Quantity" (EOQ). From the calculation results, it was found that the optimal number of fuel supply purchases from palm oil shells using the EOQ method is 352 tons with a purchase frequency of 3 times in one period (1 year) so that the company can save fuel procurement costs. . The total inventory cost of raw materials with an EOQ of Rp. 32,845,640 while the cost incurred by the company without using EOQ amounted to Rp. 34,731,000. The savings that can be made by the company is Rp. 1,885,360 with a Reorder Point of 81.9 tonnes and a total safety stock of 241 tonnes.